P282 Impact of prenatal organophosphate pesticide exposure on infant neurodevelopment in thailand. (1st September 2016) - Kongtip, Pornpimol; Techasaensiri, Benyachalee; Nankongnab, Noppanun; Adams, Jane; Phamonphon, Akkarat; Surach, Anu; Sangprasert, Supha; Thongsuksai, Aree; Srikumpol, Prayoon; Tipayamongkholgul, Mathuros; Woskie, Susan
Abstract : A longitudinal birth cohort was begun to investigate the levels and sources of pesticide exposure during pregnancy and to examine the effects of pesticide exposure on infant neurodevelopment at 5 months of age. Subjects were interviewed using questionnaires regarding their demographic characteristics, educational background, family composition, work and pesticide exposure. Also, spot urine samples were collected at 28 weeks gestation to determine maternal dimethyl phosphate (DMP), diethyl phosphate (DEP), diethyl thiophosphate (DETP), diethyl dithiophosphate (DEDTP), and total dialkyl phosphate (DAP) levels by gas chromatography-mass spectrometry. At 5 months of age, infant development was evaluated using the Bayley Scale of Infant and Toddler Development – III. Measurable levels of metabolites of organophosphate pesticides were found in urine samples from Thai women at 28 weeks of pregnancy. The primary factors that had significant influences on maternal urinary DAP concentrations were outdoor employment, farm worker jobs involving digging in the soil and applying pesticides. Prenatal organophosphate pesticide exposure, specifically maternal urinary DEDTP concentration, was significantly associated with infant cognitive, fine motor, fine and gross motor Bayley test scores (p < 0.05).